Self Healing of Cracks in Concrete with Bacteria (European Journal of Formal Sciences and Engineering, 2020)
During the service life of concrete structures, internal and external effects and micro-cracks occur in the structure. These cracks cause leakage of harmful substances into the concrete, deterioration of the strength and durability properties of the concrete, structural damages and crashes, and the high cost of maintenance and repair of the concrete structure. It is known that water-dissolved CO2 reacts with Ca+2 ions in the concrete and can repair the concrete by forming CaCO3 (limestone) crystals with very little water solubility. However, for this type of self-repair to occur, there must be water in the environment and this repair can only be made if the cracks are too small. Recently, bacterial concrete methods which has ability to self-healing are used to overcome maintenance and repair costs. In 1994, the first study on the ability to self-healing with the extra materials that were added to the concrete during the production of concrete was published by Carolyn Dry of Illinois University. Eric Schlagen and Henk Jonkers who have been researching about self-healing concrete by adding bacterial spores and calcium lactate foods to the mixture while producing concrete have made a remarkable study in this field since 2006. Bacterial concrete, Bacillus bacterial spores in the medium of the water-activated nutrients and calcium sources in the range of appropriate pH values in the concrete due to the formation of a fibrous structure is caused by precipitation of calcite. Thus, with the precipitation of calcite, the bacteria are embedded in concrete and the concrete is provided to improve itself. In previous studies, it has been shown that the cracks and voids in the concrete are filled with the ethrengeite and C-S-H structure when the control and bio-based concrete samples examined by SEM and XRD are compared. In previous studies, it was observed that mechanical strength and durability of the concrete is increased. It should be noted that the concentration of bacteria used in the solution and the ambient pH value is specified. Although conventional maintenance and repair methods are fast reacting, and short-term efficient, bacterial concrete method is sustainable, slow and long-term efficient. In addition, it is an environmentally friendly method compared to chemical repair methods and is expected to be among the remarkable materials of the future. The high initial cost leads to a reduction in producer demand, and the development process must continue to achieve the desired results and cost. As a result, it will be possible to obtain more durable structures by not wasting time, saving money and reducing the costs of high maintenance and repair. In other respects, it is a great advantage for sustainable development. Technical studies are continuing due to the high cost and laboratory test results of the bacterial family, as well as the impacts on the survival of the bacterial family. In this study, previous studies were evaluated, and some suggestions were made based on these studies.
Keywords: Self-healing concrete; micro-cracks; bacteria; humidification; bacillus pasteurii.